2002
DOI: 10.3354/dao049107
|View full text |Cite
|
Sign up to set email alerts
|

A virus-like agent associated with neurofibromatosis in damselfish

Abstract: Damselfish neurofibromatosis (DNF) is a transmissible disease involving neurofibromas and chromatophoromas affecting bicolor damselfish Stegastes partitus on Florida reefs. Analysis of genomic DNA by Southern blotting techniques demonstrated the presence of a group of extrachromosomal DNAs in tumors from fish affected with DNF but not in healthy individuals. Cell lines obtained from tumors contained identical DNAs and were shown to be tumorigenic in vivo, while lines established from healthy fish did not conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…También sería recomendable adelantar estudios que permitan estimar el tamaño efectivo poblacional para detectar poblaciones que no podrían contrarrestar los efectos de la deriva en ausencia de flujo genético (Lacy 1987) y no perder de vista factores adversos como enfermedades (Schmale et al 2002) o eventos catastróficos (Lacson y Morizot 1991) que podrían convertirse en una amenaza para estas poblaciones del Caribe por el efecto sinérgico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…También sería recomendable adelantar estudios que permitan estimar el tamaño efectivo poblacional para detectar poblaciones que no podrían contrarrestar los efectos de la deriva en ausencia de flujo genético (Lacy 1987) y no perder de vista factores adversos como enfermedades (Schmale et al 2002) o eventos catastróficos (Lacson y Morizot 1991) que podrían convertirse en una amenaza para estas poblaciones del Caribe por el efecto sinérgico.…”
Section: Discussionunclassified
“…It is therefore important to try to maintain the present levels of connectivity. It is also important to undertake studies in order to estimate the effective population size necessary to detect populations that may not counteract the effects of genetic drift or lack of gene flow (Lacy 1987), and to keep in mind other adverse factors such as sickness (Schmale et al 2002) or catastrophic events (Lacson and Morizot 1991) that could represent a threat for these populations due to synergistic effects. mitocondrial NADH1 (Rocha et al 2006), sugiriendo que los resultados no son probablemente una consecuencia de los marcadores genéticos utilizados.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion has been considered as a model for neurofibromatosis (von Recklinghausen's disease) in humans. Subsequently, it was found that the disease was transmissible from tumor-bearing to non-tumor-bearing specimens through tissue homogenates (Schmale and Hensley 1988) and that a virus-like agent, probably a retrovirus (Schmale et al 1996), was responsible for the disease in damselfish (Schmale et al 2002). Lucke (1942) reported similar nerve sheath neoplasms at a prevalence of 0.5-1.0 % in three snapper species from the Dry Tortugas near Key West.…”
Section: Neoplasmsmentioning
confidence: 99%
“…Damselfish neurofibromatosis (DNF) is one of the most extensively studied diseases of coral reef fishes (Schmale, 1991;Schmale et al, , 2002. The bicolor damselfish Stegastes partitus is a tropical marine fish on south Florida reefs that appears to be naturally affected by multiple neurofibromas, neurofibrosarcomas, and chromatophoromas.…”
Section: Tumors and Related Lesionsmentioning
confidence: 99%